Design, fabrication and analysis of a bio-based tensegrity structure using non-destructive testing. (15th August 2022) - de Albuquerque, Nathalia B.; Gaspar, Cássio M.R.; Seixas, Mario; Santana, Murillo V.B.; Cardoso, Daniel C.T.
Highlights: Bio-based tensegrity design using non-destructive static and dynamic tests. Biodegradable strut-cord joints made of bamboo full-culms and sisal ropes. The prestress level of 15% was obtained through numerical and physical scale models. No relevant loss in the prestress level during 52 days under laboratory conditions. Abstract: In this work, an experimental and numerical study of the behavior of a tensegrity structure constructed with natural materials is presented. Firstly, it is shown the concept of tensegrity structures, highlighting its emergence, current context, and applications within Civil Engineering. The design of a bio-based tensegrity structural module is investigated as object of study. Initially, a prototype of a single module of the structure is built in 1:25 scale. Subsequently, a prototype on a 1:5.65 scale is built using Phyllostachys aurea bamboo culms for the struts and sisal ( Agave sisalana ) ropes for the cable nets. Both non-destructive static and dynamic testing were performed on the module to investigate the level of prestress right after assembly of the structure and also considering the relaxation of the cable networks under laboratory conditions. The results obtained from the experimental tests are compared with the numerical predictions by means of a relative error parameter regarding the static stresses and the natural frequencies. Thus, it was possible to indirectly determine the level of prestress applied in the sisal ropes of the tensegrity module. The prestress level was equal to 15% in both static and dynamic approaches, which indicates a good agreement between them and points to the robustness of the proposed methodology. The use of bamboo as a suitable material for strut-cord joints is proposed to avoid metal components and consider the end-of-life biodegradability of the structure in the design of joints. The study deploys bio-based materials for tensegrity structures and the kit of parts as a whole, contributing to the development of extremely lightweight and sustainable structural systems.